Teacher Perceptions of the Effectiveness of Implementing the Merdeka Curriculum in Kindergarten - Sulistyowati, Winda; Wulandari, Hayani (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
The Merdeka Curriculum, a government-mandated educational policy, requires implementation across all educational levels, including early childhood education. Teachers play a pivotal role in its successful execution. To assess the effectiveness of this curriculum in a specific context, a descriptive quantitative study was conducted at the Pembina North Cikarang State Kindergarten. A questionnaire survey, utilizing a Likert scale, was administered to seven teachers to gather data on their perceptions of the curriculum's implementation. The results revealed that a significant majority of teachers (64%) strongly agreed with the curriculum's effectiveness, with an additional 31% agreeing. This positive feedback suggests that the Merdeka Curriculum is being well-received and implemented effectively in the studied kindergarten.